Exploring Gen Z English Teachers’ Challenges on ChatGPT Integration in Language Learning: English - Nanda Safitri; Nur Sobah (LET: Linguistics, Literature and English Teaching Journal, 2025)
The integration of Artificial Intelligence (AI) in language learning has emerged as a growing trend through platforms such as ChatGPT, which support creativity and teaching efficiency. However, its implementation still faces various challenges among Generation Z English teachers. Therefore, this study aims to explore the challenges, perceptions, and experiences of these teachers in integrating ChatGPT into the language learning process. Therefore, this study aims to explore the challenges, perceptions, and experiences of Generation Z English teachers in integrating ChatGPT into the language learning process. This research employed a qualitative research design using a narrative inquiry approach. The participants were four Generation Z English teachers who are actively teaching in various educational institutions. Data were collected through written interviews using a Google Form that consisted of open-ended questions, allowing participants to express their experiences in detail. The findings reveal that ChatGPT is perceived as a useful learning tool to enhance creativity, efficiency, and student engagement, yet it still encounters obstacles such as technical issues, ethical concerns, and institutional policy limitations. In conclusion, ChatGPT can serve as a valuable complement to language learning but cannot replace the essential role of teachers as primary educators.